2023
DOI: 10.1039/d2ma00878e
|View full text |Cite
|
Sign up to set email alerts
|

A review on 2D-ZnO nanostructure based biosensors: from materials to devices

Abstract: During the COVID’19 outbreak, biosensing devices won increasing relevance, demonstrating their potential in the medical diagnostic field. Hence, the present review reports on the main advances in 2D-ZnO nanostructures-based biosensors....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 234 publications
0
12
0
Order By: Relevance
“…Amongst various nanomaterial based technologies, ZNS based technology has been developed in the last few years for biosensing with different nano-architectures. [156][157][158][159][160] In the arena of respiratory virus detection, for example, an immunosensor based on patterned ZnO NR networks for the detection of influenza virus (H1N1 SIV) has been developed. 92 Here, the role of ZnO was extremely important for the immobilization of the collected antibodies on the electrode.…”
Section: Applications In Biosensingmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst various nanomaterial based technologies, ZNS based technology has been developed in the last few years for biosensing with different nano-architectures. [156][157][158][159][160] In the arena of respiratory virus detection, for example, an immunosensor based on patterned ZnO NR networks for the detection of influenza virus (H1N1 SIV) has been developed. 92 Here, the role of ZnO was extremely important for the immobilization of the collected antibodies on the electrode.…”
Section: Applications In Biosensingmentioning
confidence: 99%
“…Despite these challenges, significant progress has been made in recent years in understanding the toxicological implications of ZNSs. One of the key findings is that ZnO NPs can generate ROS, 245 which can damage cells and lead to inflammation. ROS generation is thought to be one of the main mechanisms by which ZnO NPs exert their toxic effects.…”
Section: Toxicological Implications and Clinical Translation Of Zno-b...mentioning
confidence: 99%
“…SnO 2 is a metal oxide that is frequently used in non-biological sensors, although it is susceptible to interference from humidity and other analytes, which can lower its selectivity towards particular target analytes. On the other hand, it has been demonstrated that zinc ZnO [47] sensors have a higher sensitivity to some analytes, although they can be less repeatable due to fluctuations in the growth conditions of the thin films used in their production [48]. While the selectivity and sensitivity of other metal oxides, such as tungsten oxide (WO 3 ) [49] and titanium dioxide (TiO 2 ) [50], have shown encouraging results, other variables, including the crystal structure, doping concentration, morphology and operation temperature, can also affect how well these materials work.…”
Section: Current and Future Challengesmentioning
confidence: 99%
“…[248] ZnONPs deliver high adsorption efficiency towards many biomolecules, as their isoelectric point (pI) of 9.5 promote strong attractive coulombic forces with lower pI bioreceptors. [249] The above-mentioned FETimmunosensor was able to detect HSA with a sensitivity of 0.826 mA/(g/mL), exhibiting a wide linear range between 0.01 and 100 mg/mL and LOD = 9.81 ng/mL. TiS 3 nanoribbons (TiS 3 NRBs) of some nanometres thick and width lower than 500 nm also represented a good choice as a channel material in IMFET design for detecting CA 19-9 pancreatic cancer marker.…”
Section: Field-transistor Effect Immunosensorsmentioning
confidence: 99%
“…ZnONRs have been used for modifying a SiO 2 transducer in a FET‐immunosensor for human serum albumin (HSA), highly improving the availability of binding sites for the related Ab [248] . ZnONPs deliver high adsorption efficiency towards many biomolecules, as their isoelectric point (pI) of 9.5 promote strong attractive coulombic forces with lower pI bioreceptors [249] . The above‐mentioned FET‐immunosensor was able to detect HSA with a sensitivity of 0.826 mA/(g/mL), exhibiting a wide linear range between 0.01 and 100 mg/mL and LOD=9.81 ng/mL.…”
Section: Detection Techniquesmentioning
confidence: 99%